COMPARATIVE CLINICAL AND BIOMECHANICAL DATA OF OSTEOSYNTHESIS FOR DISLOCATED CLAVICLE BODY FRACTURES WITH COMPRESSION ROD - Гапон, Олександр (SWorldJournal, 2025)
The accepted method of treatment for displaced clavicle fractures is surgical - various implants are used for osteosynthesis, with contoured LCP plates and intramedullary rods being preferred. When using the latter, typical complications may arise, such